Event-Based LQR Control for Rotary Inverted Pendulum Using Wireless Networked Control System - Thongsakul, Baitong; Numsomran, Arjin; Tipsuwanporn, Vittaya; Chaoraingern, Jutarut (My University, 2023)
Wireless communication introduces delays, packet losses, and data uncertainties, which can degrade the control's performance. To address these challenges, this paper presents an event-based Linear Quadratic Regulator (LQR) control approach for a rotary inverted pendulum system utilizing a Wireless Networked Control System (WNCS). To facilitate the control process, a WNCS is employed to transmit data between the rotary inverted pendulum and the controller via WiFi, a wireless network executing in the CYW43439 wireless chip of the Raspberry Pi Pico W development board. The wireless node consists of a sensor node, actuator node, access point node, and controller node, which transmit and receive data via the TCP/IP communication protocol. The event-triggering mechanism is integrated into the control loop. It allows the control algorithm to adaptively adjust the control update rate based on the system's dynamics and network conditions, ensuring efficient utilization of network resources while maintaining satisfactory control performance. The experimental results of hardware in the loop (HIL) in the MATLAB/Simulink real-time kernel show that the proposed event-based LQR control strategy can achieve balancing and improve resilience to network-induced disturbances, making it suitable for real-world applications where wireless network constraints are prevalent.
Keywords: Event-based LQR control; IEEE 802.11n; Raspberry Pi Pico W; Rotary inverted pendulum; WNCS